Effect and individual response to inspiratory muscle training program among instrumentalist musicians - Ibáñez-Pegenaute, Ana; Ortega-Moneo, María; Ramírez-Vélez, Robinson; Antón, M. M. (Frontiers in Physiology, 2024)
In this quasi-experimental before-after trial, we investigated the effects of a high-intensity, low-repetition inspiratory muscle training (HI-LRMT) protocol on respiratory muscle strength in instrumental musicians. In addition, was to estimate the prevalence of “non-responders” (NRs) in terms of muscle force after intervention. Healthy musicians (n = 48) were divided into 2 groups: HI-LRMT (n = 33) and a control group that did not train (CG, n = 15). The intervention training was a high-intensity, low-repetition inspiratory muscle training program using the PowerBreathe® threshold load pressure device, 2 daily sessions of 30 repetitions per session, with a minimum frequency of 5 days per week, for 12 weeks, 5 min per session. The primary outcome measures were maximal inspiratory pressure and expiratory pressure. Change in PImax over 12 weeks for HI-LRMT vs. control was 30.9 (95% CI 25.5–38.3), with the large effect, confirming worthwhile benefits (ηp2 = 0.61). There were significant changes in PEmax 37.3 (95% CI 19.3–48.1), with a large effect size (ηp2 = 0.33). A third of the participants did not demonstrate improvements in terms of muscle force in instrumental musicians. In conclusion, a 12-week high-intensity, low-repetition inspiratory muscle training program using the PowerBreathe® threshold load pressure device, improved inspiratory and expiratory muscle strength in instrumental musicians.